PENGARUH KEMUDAHAN PENGGUNAAN DAN KEAMANAN TRANSAKSI TERHADAP MINAT PENGGUNAAN METODE PEMBAYARAN QRIS MELALUI KEPUASAN PENGGUNA PADA MAHASISWA FAKULTAS EKONOMI UNIVERSITAS NEGERI JAKARTA - Achmad Zaky Maulana; Muhamad Aqdi Alhamro, Naufal Dwiranzah, Ridho Sandy Pramudita, Rafilino Rianda Sastrodiningrat (CV. Adiba Aisha Amira, 2025)
The use of QRIS has become a necessity for individuals in daily transactions. This research will examine the influence of Ease of Use and Transaction Security on the Intention to Use the QRIS Payment Method through User Satisfaction. This research employs a quantitative method, with 100 respondents. Based on the collected data, the most respondents are between the ages of 19 and 21, and they are students from a public university in Jakarta. The analysis method used for the data is Structural Equation Modeling (SEM) with a Partial Least Squares (PLS) approach, using the SmartPLS 4 software. The analysis results show that ease of use and transaction security have a significant direct impact on the intention to use the QRIS payment method. The results also indicate that, indirectly, both variables show significant results using user satisfaction as the mediating variable.